An item response analysis of the pediatric PROMIS anxiety and depressive symptoms scales. - Irwin DE; Stucky B; Langer MM; Thissen D; Dewitt EM; Lai JS; Varni JW; Yeatts K; DeWalt DA; Irwin, Debra E; Stucky, Brian; Langer, Michelle M; et al. (Quality of Life Research, 2010)
Purpose: The Patient-Reported Outcomes Measurement Information System (PROMIS) aims to develop self-reported item banks for clinical research. The PROMIS pediatrics (aged 8-17) project focuses on the development of item banks across several health domains (physical function, pain, fatigue, emotional distress, social role relationships, and asthma symptoms). The psychometric properties of the anxiety and depressive symptom item banks are described.Methods: Participants (n = 1,529) were recruited in public school settings, hospital-based outpatient and subspecialty pediatrics clinics. The anxiety (k = 18) and depressive symptoms (k = 21) items were split between two test administration forms. Hierarchical confirmatory factor-analytic models (CFA) were conducted to evaluate scale dimensionality and local dependence. IRT analyses were then used to finalize item banks and short forms.Results: CFA results confirmed that anxiety and depressive symptoms are separate constructs and indicative of negative affect. Items with local dependence and DIF were removed resulting in 15 anxiety and 14 depressive symptoms items. The psychometric differences between short forms and simulated computer adaptive tests are presented.Conclusions: PROMIS pediatric item banks were developed to provide efficient assessment of health-related quality of life domains. This sample provides initial calibrations of anxiety and depressive symptoms item banks and creates PROMIS pediatric instruments, version 1.0.